Underwater Shock Response of Circular HSLA Steel Plates - R. Rajendran; K. Narasimhan (Shock and Vibration)
Studies on shock response of circular plates subjected to underwater explosion is of interest to ship designers. Non-contact underwater explosion experiments were carried out on air backed circular High Strength Low Alloy (HSLA) steel plates of 4 mm thickness and 290 mm diameter. The experiments were carried out in two phases. In the first phase, strain gauges were fixed at intervals of 30 mm from the centre of the plate and strains were recorded for the shock intensity gradually increasing to yielding. Semi-analytical models were derived for the elastic strain prediction which showed good agreement with the experiments. Dynamic yield stress and the shock factor for yielding were established. In the second phase, individual plates were subjected to increasing shock severity until fracture and the apex bulge depth and the thickness strains were measured. Empirical models were derived to predict the plastic deformation which were validated through a fresh set of experiments. Analysis of the fractured surface by visual examination showed that there was slant fracture indicating ductile mode of failure and the same was corroborated by Scanning Electron Microscopic (SEM) examination.